Peran Guru Dalam Pengembangan Literasi Digital - Dian Nastiti; Indah Ayu Permana P (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
This Community Service Program examines efforts to enhance teachers' digital literacy in online learning. In the era of information technology, information and digital literacy have become crucial. The execution of this Community Service Program aims to improve teachers' understanding of digital literacy. This activity is conducted online in the second weeks of June and July. The provided topics include "Digital Literacy and Its Urgency in Today's Education," "Myths and Misconceptions about Literacy," and "Digital Literacy." The Community Service Team consists of two lecturers from Nahdlatul Ulama University Purwokerto, namely Dian Nastiti, M.Pd., and Indah Ayu Permana Pribadi, S.IP., M.Sos, with student participation. Data is analyzed descriptively and qualitatively to identify potential improvements through this program. The results of this program demonstrate that teachers at MI Maarif Nu Attijani are able to apply digital literacy in online learning. They effectively utilize platforms and instructional media with the guidance of the program team. This research emphasizes the importance of digital literacy for teachers and the success of the program in enhancing the utilization of technology in online learning.